Adapting to change : the business of climate resilience - Goodman, Ann. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
This book examines emerging business reactions to, plans, and preparations for climate events (e.g., fires, storms, floods, and hurricanes) and trends (e.g., droughts) from leading companies in strategic sectors: technology, telecommunications, food, banking, and insurance.
1. Responding to weather -- 2. Learning from disaster -- 3. Doing more with less -- 4. Taking a risk, and managing it -- 5. Communicating change, collaborating on climate -- Conclusion -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on September 14, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Emergency management; Climatic changes -- Economic aspects; Organizational change -- Management; business; Climate change/adaptation; disaster; global warming; green; sustainability; resilience; risk; risk management; sustainable development; uncertainty; weather; UN; IPCC; NCA; COP 21; Electronic books